Karsten’s Work as a City Branding Strengthener for The Semarang City, Indonesia - Albertus Sidharta Muljadinata; Bayu Widiantoro (ARCHIHUMANUM, 2023)
Currently the City of Semarang, Indonesia, is trying to have a BRAND which is expected to be able to show the potential of Semarang city. Semarang city is one of the cities in Indonesia which in planning the development of the form of town planning, was planned by a city planner who is also an architect named Ir. Herman Thomas Karsten. Karsten has a lot of architectural works in Semarang city, ranging from buildings that function as houses, offices, to other public buildings such as schools, markets, theater, office building, housings, and hospitals. Karsten's architectural works are known to be comfortable to view or use for their activities. This is shown by the many works of Karsten which are still being used well by building users. This study aims to reveal the potential of the city of Semarang related to the urban cultural heritage of Karsten's work. This research will provide benefits for the stakeholders of the Semarang City in determining the city branding of Semarang city. In addition, this research is also beneficial for the development of architectural scholarship, and will provide new insights to the academic community about the importance of cultural heritage in a city. This research will provide clarity, that the Urban Cultural Heritage will affect the city identity and city character. As for the community, this research will contribute to helping the creation of a new built environment for cultural heritage artifacts through the city's brand image.